The Impact of Brand Love, Customer Satisfaction, and Word of Mouth on Cosmetic Purchase Intention - Gilang Pratama Hafiz; Zahwa Arsyi Maulida (Universitas Mercu Buana, 2023)
This study was conducted to explore The Impact of Brand Love, Customer Satisfaction and Word of Mouth on Luxcrime Cosmetics Purchase Intention. The contribution of this research is expected to be able to add information at the theoretical/scientific level of marketing management and also provide an increase in Service Excellent in the cosmetic industry sector. Primary data in this study were collected through questionnaires with a total of 260 respondents who live in Jabodetabek and have purchased Luxcrime brand cosmetic products and used this product more than once. The data analysis technique used by researchers in this study is partial least squares structural equation modeling. The results of this study indicate that six of the seven proposed hypotheses are accepted, while Brand Image cannot affect Brand Love. To make brand marketing more effective, marketers need to be aware of the emotional component of the company. In addition, achieving the highest level of brand love for a cosmetic brand can be an innovation for long-term success. For further research, researchers can expand research both from the demographics of research locations in Indonesia.